2018
DOI: 10.14701/ahbps.2018.22.4.310
|View full text |Cite
|
Sign up to set email alerts
|

A composite of urinary biomarkers for differentiating between tubulointerstitial inflammation and interstitial fibrosis/tubular atrophy in kidney allografts

Abstract: Backgrounds/AimsCompared with a single urinary biomarker, a composite of multiple urinary biomarkers may be more helpful for differentiating tubulointerstitial inflammation from interstitial fibrosis/tubular atrophy (IFTA) in kidney allografts.MethodsIn this cross-sectional cohort study, we collected urine samples from 115 patients with for-cause biopsy, 53 patients with stable allografts, and 50 living kidney donors. We measured the urinary levels of transglutaminase 2 (TG2), syndecan-4 (SDC4), alpha 1 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Richardson et al [27] analyzed HSPG localization in corneal fibroblasts and revealed that the nuclear localization of HSPG core proteins was greater in fibronectin cells and proposed that fibronectin-mediated nuclear localization of HSPG might play an important role in inducing biological responses and regulating nuclear function. We have previously reported composition of urinary TG2, SDC4, IP-10, and MCP-1 as potent biomarkers to distinguish IFTA from tubulointerstitial inflammation in kidney transplant recipients [28]. To our knowledge, this is the first study to verify the value of urinary TG2 as a biomarker for allograft fibrosis and IFTA in deceased donor kidney transplant patients.…”
Section: Discussionmentioning
confidence: 83%
“…Richardson et al [27] analyzed HSPG localization in corneal fibroblasts and revealed that the nuclear localization of HSPG core proteins was greater in fibronectin cells and proposed that fibronectin-mediated nuclear localization of HSPG might play an important role in inducing biological responses and regulating nuclear function. We have previously reported composition of urinary TG2, SDC4, IP-10, and MCP-1 as potent biomarkers to distinguish IFTA from tubulointerstitial inflammation in kidney transplant recipients [28]. To our knowledge, this is the first study to verify the value of urinary TG2 as a biomarker for allograft fibrosis and IFTA in deceased donor kidney transplant patients.…”
Section: Discussionmentioning
confidence: 83%
“…The aim of our study was to identify indicators of tubular damage in stable LN patients and to correlate them with kidney biopsy findings. We selected a panel of tubular biomarkers that have been correlated with interstitial fibrosis and cortical interstitial inflammation in different CKD populations: α1‐mcg, β2‐mcg, UMOD, NGAL, KIM‐1, MCP‐1, and uDKK3 19–24 …”
Section: Introductionmentioning
confidence: 99%
“…We selected a panel of tubular biomarkers that have been correlated with interstitial fibrosis and cortical interstitial inflammation in different CKD populations: α1-mcg, β2-mcg, UMOD, NGAL, KIM-1, MCP-1, and uDKK3. [19][20][21][22][23][24] 2 | ME THODS…”
mentioning
confidence: 99%
“…[2][3][4] Meanwhile, glomerular dysfunction and morphological changes that lead to subsequent development of glomerulosclerosis and nephron dropout will be seen with or without tubular atrophy, tubulointerstitial fibrosis and renal arteriolar hyalinosis. [5][6][7][8] Although the progression of DKD could be slowed with tight glycemic control and antihypertensive/lipid-lowering therapies, these interventions do not prevent the progress of DKD to end stage of renal disease (ESRD) or renal failure. 9 Chronic inflammation in the kidney plays a key role in the development and progression of DKD.…”
Section: Introductionmentioning
confidence: 99%